Studies of elementary reactions of interest in hydrocarbon pyrolysis - Lightfoot, P; Phillip D Lightfoot (1986)
﻿ A novel hydrogen atom source, involving the 193.3 nm photolysis of nitrous oxide in the presence of hydrogen, is described. The system is shown to provide a very clean source of hydrogen atoms, particularly at temperatures above 400K. The H + C2H4 addition reaction is studied as a function of pressure (50-750 Torr He) and temperature (285-604K). Resonance fluorescence was used to monitor hydrogen atom concentrations in real time, following excimer (ArF) photolysis of the N20/H2 precursor. The data are analysed using the Troe factorisation method. A model is developed, which allows the accurate calculation of the rate constant for the H + C2H4 reaction over a wide range of temperature and pressure. The direct observation of equilibration in the H + C2H4 = C2H5 system is reported for the first time, at temperatures between 775 and 850K. Hydrogen atom concentrations were monitored by resonance fluorescence, following 193.3 nm photolysis of the ethylene substrate. The equilibrium constant for the system Kc is determined much more precisely than has previously been possible. The standard heat of formation of the ethyl radical, ΔHof, 298(C2H5), is evaluated from the measured values of Kc(T), using Third Law methods and the known molecular and atomic parameters of H, C2H4 and C2H5 giving ΔHof 298(C2H5) = 28.36 ± 0.40 kcalmol . The quoted errors refer to 95.45% confidence limits and include contributions from the scatter of the data and from estimates of possible systematic errors. An excimer laser flash photolysis/ gas chromatographic end product analysis apparatus is described. The design of the photolysis cell allows its entire contents to be transferred to the analysis column, and enables total C3 hydrocarbon yields as low as 2.6x1012 molecules to be detected. A study of the photolysis of acetone at 193.3 nm is presented. The dependence of product yields on pressure (10-500 Torr He), temperature (300,600K), laser pulse energy and the presence of radical scavengers (NO,C2H4) is described. Under all experimental conditions, methyl radicals account for >95% of the radical products of the photolysis. The ArF photolysis of acetone is demonstrated to provide a very clean source of methyl radicals, suitable for use in conventional laser flash photolysis /kinetic spectroscopy experiments, at temperatures of up to 825K. Experiments are described, in which ethane and ethane/propylene mixtures, diluted to ∿5% in nitrogen, were pyrolysed in a quartz jetstirred reactor. Temperatures and conversions comparable to those achieved in industrial pyrolysis were employed. A kinetic model of ethane pyrolysis is developed, which qualitatively reproduces the experimental results. It is shown that the model predictions are extremely sensitive to a number of poorly defined rate constants.